Beyond straight A's - Abd Razak, Dzulkifli (2005)
Even at Oxford, critics are saying that students can achieve faultless results but lack intellectual curiosity. OXFORD is one of the world’s oldest universities in the world and, while participating in the Round Table on Higher Education Leadership there recently, I appreciated its meticulous education system. Based on centuries of tradition, students are individually tutored after being handpicked through a laborious application and interview process. Oxford is one of the few universities in the world, and one of the two in Britain (the other being Cambridge), that is steeped in tradition. Evidently, even Oxford is not spared some sort of criticism for reforms. How this will shape Oxford is anyone’s guess. For sure, among the world’s best, too, there are problems.